Determination of electrokinetic and hydrodynamic parameters of proteins by modeling their electrophoretic mobilities through the electrically charged spherical soft particle - Deiber, Julio Alcides (2013)
This work explores the possibility of using the electrically charged "spherical soft particle" (SSP) to model the electrophoretic mobility of proteins in the low charge regime. The general framework concerning the electrophoretic mobility of the SSP already presented in the literature is analyzed and discussed here in particular for polyampholyte-polypeptide chains. In this regard, this theory is applied to BSA for different protocol pH values. The physicochemical conditions required to model proteins as SSP from their experimentally determined electrophoretic mobilities are established. In particular, the protein charge regulation phenomenon and the SSP particle core are included to study BSA having isoelectric point pI ≈ 5.71, within a wide range of bulk pH values. The results of this case study are compared with previous ones concerning the spherical porous particle and the spherical hard particle with occluded water. A discussion of chain conformations in the SSP polyampholyte layer is presented through estimations of the packing and friction fractal dimensions.